Dirofilaria immitis exposure status in client-owned cats with or without lower airway/lung-associated signs: case-control study in a canine heartworm-endemic area. Issue 2 (February 2017) - Lin, Chung-Hui; Lo, Pei-Ying; Tsai, Han-Ju; Wang, Lih-Chiann; Liaw, Bor-Song; Hsieh, Olivia F; Chang, Yeong-Shuenn; Tsai, Yi-Chin; Yu, Szu-Ching; Chueh, Ling-Ling
Objectives: Heartworm-associated respiratory disease (HARD) is a recently recognised pathological manifestation in cats caused by Dirofilaria immitis exposure. This study aimed to estimate the percentage of cats at risk of developing HARD in a heartworm-endemic area (Taipei, Taiwan), and to test the correlation of heartworm exposure and the presence of lower airway/lung clinical signs (LA/L signs). Methods: This was a prospective case-control study. The study design called for the enrolment of at least 80 cats with LA/L signs and at least 80 cats without such clinical signs in a 1 year period. The D immitis antibody seroprevalence of the two cohorts was compared. Results: From February 2014 to January 2015, 187 client-owned cats were prospectively enrolled: 83 clinical cases with LA/L signs and 104 cats without such signs. Antibody seropositivity was approximately twice as frequent in cats with LA/L signs (13.3%) than in cats without signs (7.8%) (odds ratio [OR] 1.814); nevertheless, no statistically significant difference between the two cohorts ( P = 0.22) was found. We used 41 frozen samples from free-roaming cats to examine the possibility of different exposure rates to mosquito bites between client-owned cats and stray cats, finding the seroprevalence to be 7.5% in free-roaming cats – a result not statistically different to that in client-owned cats ( P = 0.60). Outdoor access was a significant risk factor for heartworm exposure in client-owned cats (OR 3.748; P = 0.03); however, living entirely indoors did not provide complete protection from exposure/infection. Conclusions and relevance: Our results did not show statistically significant differences in antibody seroprevalence between cats with and without LA/L signs. LA/L signs were not always present under conditions of natural exposure. However, exposure to D immitis is not rare among client-owned cats, suggesting that heartworm prophylactics should be a part of routine care in all cats living in areas endemic for canine heartworm.